Research priorities set by people with OCD and OCD researchers: Do the commonalities outweigh the differences? - Franziska Kühne; Anna Levke Brütt; Mara Jasmin Otterbeck; Florian Weck (Wiley, 2021)
Abstract Objective In contrast to research agendas being predominantly set by scientists or funders, a collaborative approach was used to spot future goals for research on obsessive‐compulsive disorder. Methods First, we conducted a meta‐review and then compared the results of two online surveys with OCD professionals and patients on research priorities. The literature search was performed in three comprehensive databases, and ten research goals were extracted. Sixty‐four patients and eight professionals responded to open questions on their five most important goals. Then, they ranked the ten aims extracted from the literature on a 6‐point Likert scale. Results For patients and professionals, research on treatment gains that persist long‐term was most important. Concerning the top five goals listed in an open format, for patients, development and maintenance of the disease was as important as psychotherapy and its efficacy. In contrast, for professionals, the efficacy and the optimization of psychotherapy were the far most important research goals. Conclusions We proposed one possibility to involve patients in OCD research, and the multitude of answers presents a wealth of research ideas. Practice Implications Since consistent research involvement may contribute to its clinical impact, researchers are now invited to translate our findings into empirical studies.